Once a Chinese International Student and Now an English Professor: An Autoethnographic Self-Inquiry of Journeys Against Linguicism and Monolingual Ideologies - Zhang-Wu, Qianqian (Journal of International Students, 2022)
In this autoethnographic critical self-inquiry study, I draw upon my unique identity as once a Chinese international student and now an English professor at a private research university in the United States to investigate how I sought for my multilingual identity and empowered my international students while coping with linguicism and monolingual ideologies. Despite the increasing cultural and linguistic diversity in student population, the faculty body in degree-granting postsecondary institutions remains dominated by White, native speakers of English (National Center for Education Statistics, 2019). Such a lack of diversity in the faculty body is present especially in the field of English, where monolingualism and nativeness is often the unspoken norm (Nigar & Kostogriz, 2019). This has exerted far-reaching impacts on all facets of English language teaching, posing substantial challenges to the professional development, instructional practices, and identity negotiation among nonnative English-speaking faculty of color. In this autoethnographic critical self-inquiry study, I reflected on my identity as once a Chinese international student and now an English professor to explore: • How did my non-whiteness and non-native-English-speakerness affect my identity and self-positioning as a Chinese international student and an English professor? • How did I cope with linguicism and monolingual language ideologies in American higher education and beyond? Autoethnography is a helpful approach to systematically explore one’s personal experiences from unique cultural perspectives (Ellis & Bochner, 2006). Critical self-inquiry is an essential research methodology to investigate tensions between belief systems and about identities (Larrivee, 2000; Marshall, 2001). Integrating the two methods together, autoethnographic critical self-inquiry allows exploration of lived experiences from an emic stance while acknowledging the dynamics of identity shifts and interaction. This autoethnographic critical self-inventory study focused on my journeys as once a Chinese international student (2012-2019) and later an English professor (2019-current) in American higher education. Following the critical self-inventory model (Allard & Gallant, 2012; Attard, 2014), data were collected to reflect both my on-going self-reflections (my teaching journals and diaries) and my conversing with others, including recordings and documentations of my interactions with colleagues and students. Data were analyzed following the coding procedures of applied thematic analysis (Guest et al., 2011) to explore important storylines in order to bring "readers into the scene" through showing and telling (Ellis, 1993, p. 711). Preliminary findings show that while my non-whiteness and nonnativeness have posed challenges to my initial self-positioning as a legitimate member in American higher education, I gradually transitioned my self-perceived “otherness” into my unique advantage as a multilingual expert with lived experiences as a means to fight against linguicism. Consequently, I was able to draw upon my lived identities to serve as a role model to empower my students which in turn empowered myself.